Ser cego: implicações do/no processo de formação identitária da pessoa - Carvalho, Merislandia Paulo da Silva (2021)
This study aimed to analyze the constitution of the identity formation processes of three blind people, congenital or acquired, through their life history, based on the central axes: family, community and school. As a theoretical perspective, it counts on the contributions of Boaventura de Sousa Santos, which brings some concepts, premises and/or guidelines, problematizing the experience of/by people involved in the research. Qualitative in nature, it assumes the life story as a theoretical-methodological perspective, in which, when narrating, the person can give greater or lesser emphasis to the facts, creating possibilities and meanings based on the experience and reflecting on the situation. Data composition used instruments such as a block of questions with broad themes and recurring interviews. Three women living in Espírito Santo participated in the study. Data analysis indicates that family knowledge about the possibilities of blind people to relate to their environment influences the study participants' autonomy, outlining the ongoing processes of identity formation. Thus, the more opportunities they were given, the greater the advances towards freedom and autonomy. The data show that family members who enable greater interaction with the environment, believing in the potential of the blind person, contact in different spaces and with people who circulate in such environments, games with colleagues and the various opportunities to experience the world, in addition of providing greater knowledge of their possibilities, they influence self-confidence, translating into greater opportunities in their path. The information is sometimes presented with strong traces of schooling in an inclusive perspective, sometimes permeated by excluding situations, which bring to the blind person impotence and discomfort, often profound, while schooling from an inclusive perspective translates into important moments of belonging from the effective participation in the school context, with the blind student having the right to schooling guaranteed, with access, permanence and learning in the process. These facts encourage us to continue the struggle for citizen lives.